Clinical Imaging of Choroid Plexus in Health and in Brain Disorders: A Mini-Review - Hubert, Violaine; Chauveau, Fabien; Dumot, Chloé; Ong, Elodie; Berner, Lise-Prune; Canet-Soulas, Emmanuelle; Ghersi-Egea, Jean-François; Wiart, Marlène (Frontiers in Molecular Neuroscience, 2019)
The choroid plexuses (ChPs) perform indispensable functions for the development, maintenance and functioning of the brain. Although they have gained considerable interest in the last years, their involvement in brain disorders is still largely unknown, notably because their deep location inside the brain hampers non-invasive investigations. In-vivo iImaging tools have become instrumental to the diagnosis and pathophysiological study of neurological and neuropsychiatric diseases. This review summarizes the knowledge that has been gathered from the clinical imaging of choroid plexusesChPs in health and brain disorders not related to ChP pathologies. Results are discussed in the light of pre-clinical imaging studies. As seen in this review, to date, most clinical imaging studies of ChPs have used disease-free human subjects to demonstrate the value of different imaging biomarkers (ChP size, perfusion/permeability, glucose metabolism, inflammation…), sometimes combined with the study of normal ageing. Although very few studies have actually tested the value of ChP imaging biomarkers in patients with brain disorders, these pioneer works studies identified ChP changes that are promising data for a better understanding and follow-up of diseases such as schizophrenia, epilepsy and Alzheimer’s disease. In-vivo imaging Imaging of immune cell trafficking at the ChPs has remained limited to pre-clinical studies so far but has the potential to be translated in patients for example using MRI coupled with the injection of iron oxide nanoparticles. Future works investigations should aim at confirming and extending these findings and at developing translational molecular imaging tools for bridging the gap between basic molecular and cellular neuroscience and clinical research.